Children with congenital colorectal malformations often require special education or remedial teaching, despite normal intelligence. (28th October 2015) - van den Hondel, Desiree; Aarsen, Femke K.; Wijnen, Rene M.H.; Sloots, Cornelius E.J.; IJsselstijn, Hanneke
Abstract: Aim: This study prospectively evaluated neuropsychological functioning in 8‐year‐old patients with anorectal malformation (ARM) and Hirschsprung's disease (HD). Methods: School functioning and behaviour were assessed in a standardised interview. Intelligence, attention, self‐esteem and quality of life were evaluated with validated tests and questionnaires. The following predictors were assessed: socio‐economic status, number of episodes of general anaesthesia, laxative treatment and premature birth. Severely intellectually disabled patients were excluded. Results: In total, twelve of the 23 (52%) patients with ARM and 11 (55%) of the 20 patients with HD received special education or remedial teaching. The intelligence quotient was normal: mean (standard deviation or SD) was 98 (17) and 96 (17), respectively. However, sustained attention was below the norm: mean (SD) Z‐score was −1.90 (1.94) and −1.43 (1.98) for ARM and HD patients; both p < 0.01. Self‐esteem was normal: mean (SD) Z‐score was 0.10 (1.29) and −0.20 (1.11) for ARM and HD patients. Quality of life was normal in ARM patients and slightly impaired in HD patients. No predictors for neuropsychological outcome were identified. Conclusion: Despite normal intelligence, more than half of these patients received special education or remedial teaching. In addition, problems with sustained attention were found. These findings are important for long‐term care.